A contribuição de Diké na formação do Emílio ou o papel da jurisdição constitucional na concretização do direito social à educação - Castro, Felipe Araújo (2014)
The fundamental social right to education has a lengthy constitutional argument, having been declared as a right to everyone in the Title dedicated to the fundamental rights and warrants and, later, scrutinized in the Social Order Chapter exclusively devoted to this theme, where specific rights are guaranteed and fundamental duties are imposed to family, society, and state. In that which concerns education, the 1988 Constitution is the result of a historical-normative process which, since the days of the Lusitanian Empire wavering between distinct levels of protection warrants in some way the educational process. Nevertheless, not even the State s oldest commitment to education has been fully achieved, namely, the annihilation of illiteracy. Even as other fundamental social rights, education is inflicted with the lack of effective political will to reach its fulfillment, and this is reflected in the production of doctrine and jurisprudence which reduce the efficacy of these rights. The objective of this work is to analyze what part is to be played by the constitutional jurisdiction in the reversal of this picture in regards to the fulfillment of the fundamental social right to education. Therefore it is indispensable to present a proper conception of constitutional jurisdiction its objectives, boundaries and procedures and that of the social rights in the Brazilian context so as to establish its relationship from the prism of the right to education. The main existing obstacles to the effective action of constitutional jurisdiction on the ground of social rights are identified and then proposals so as to overcome them are presented. The contemplative and constructive importance of education in the shaping of the individual as well as its instrumental relevance to the achievement of the democratic ideal through the means of the shaping of the citizen is taken into account. The historical context which leads to the current Brazilian educational system is analyzed, tracing the normative area and the essential content of the fundamental right to education aiming to delineate parameters for the adequate development of the constitutional jurisdiction in the field. This jurisdiction must be neither larger nor narrower than that which has been determined by the Constitution itself. Its activity has been in turns based on a demagogic rhetoric of those fundamental rights which present a doubtful applicability, or falling short of that which has been established showing an excessive reverence to the constituent powers. It is necessary to establish dogmatic parameters for a good action of this important tool of constitutional democracy, notably in regards to the fundamental social right to education, for the sake of its instrumental role in the achievement of the democratic ideals of liberty and equality